The Role of Knowledge Management in Small Project Management Afield Study in Oxygen Ahli Plant in Iraq - العيساوي, خالد عبد الله; شاكر, شذى عبود (Journal of Economics and Administrative Sciences, 2018)
Most of the literature on the management and application terkzat waved the last period on large organizations was the negligence  of  knowledge management in small organizations where research aims to find out knowleddge management, small projects  In oxygen Ahli plant in Iraq, and the fact the role of knowledge management in small projects from the standpoint of employees in order to achieve this used production method results.  The results showed that knowledge management has a role in the high level of productivity during the years 2010-2013. The results showed that knowledge management has a role in the high level of productivity during the years 2010-2013 based on the results researcher recommended strengthening the role of knowledge management in oxygen Ahli plant in Iraq because of their role in the management of small enterprises, which can be lifted to improve the economic and social level and increase productivity, this study aimed at addressing some of the imbalances in the literature through the development of knowledge management in the field of small organizations of the business, that is, they look at the advantages and its competitors and disadvantages and strengths and weaknesses and problems Home associated with all of them with knowledge managment.